Comparison of Three Sample Preparation Procedures for the Quantification of L-Arginine, Asymmetric Dimethylarginine, and Symmetric Dimethylarginine in Human Plasma Using HPLC-FLD - Anne Marie Voigt Schou-Pedersen; Jens Lykkesfeldt (Journal of Analytical Methods in Chemistry)
Increased asymmetric dimethylarginine (ADMA) in human plasma has been associated with reduced generation of nitric oxide, leading to atherosclerotic diseases. ADMA may therefore be an important biomarker for cardiovascular disease. In the present study, three sample preparation techniques were compared regarding the quantification of L-arginine and ADMA in human plasma: (A) protein precipitation (PP) based on aqueous trichloroacetic acid (TCA), (B) PP using a mixture of ammonia and acetonitrile, and (C) solid-phase extraction (SPE). The samples were analysed by using high-performance liquid chromatography with fluorescence detection (HPLC-FLD). The analytical performance of (A) was comparable with that of (C), demonstrating recoveries of >90%, coefficient of variations (CVs, %) of <8, and a resolution (Rs) between ADMA and symmetric dimethylarginine (SDMA) of 1.2. (B) was disregarded due to recoveries below 75%. (A) was validated with good results regarding linearity (>0.994), precision (<5%), and sensitivity (lower limit of quantification (LLOQ)) of 0.14 µM and 12 nM for L-arginine and ADMA, respectively. Due to the simplicity and speed of procedure (A), this approach may serve as preferred sample preparation of human plasma samples before HPLC-FLD in providing important information regarding elevated ADMA concentrations.